2015
DOI: 10.1016/j.phytochem.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of the plant cell wall in gravity resistance

Abstract: Gravity resistance, mechanical resistance to the gravitational force, is a principal graviresponse in plants, comparable to gravitropism. The cell wall is responsible for the final step of gravity resistance. The gravity signal increases the rigidity of the cell wall via the accumulation of its constituents, polymerization of certain matrix polysaccharides due to the suppression of breakdown, stimulation of cross-link formation, and modifications to the wall environment, in a wide range of situations from micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…Among these environmental changes, the effects of gravity on land may undoubtedly have induced alterations in the physiology, anatomy, and growth of bryophytes, extrapolated from previous findings obtained from vascular plants. Gravity influences the physiological processes of vascular plants including long-distance water transport (Lambers et al 2008), leaf gas exchange (Hirai and Kitaya 2009), cell proliferation (Matía et al 2010), and cell wall rigidity (Hoson and Wakabayashi 2015) and, thus, plant growth (Hangarter 1997). Nevertheless, few studies have investigated the gravitational responses of bryophytes even though gravitropism has been extensively examined (Banbury 1962; Cove and Quatrano 2006; Martin et al 2009; Repp et al 2004; Schwuchow et al 2002); only one study showed the significant effect of microgravity on the growth pattern of the dark-grown protonemata of the moss Ceratodon purpureus (Kern et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among these environmental changes, the effects of gravity on land may undoubtedly have induced alterations in the physiology, anatomy, and growth of bryophytes, extrapolated from previous findings obtained from vascular plants. Gravity influences the physiological processes of vascular plants including long-distance water transport (Lambers et al 2008), leaf gas exchange (Hirai and Kitaya 2009), cell proliferation (Matía et al 2010), and cell wall rigidity (Hoson and Wakabayashi 2015) and, thus, plant growth (Hangarter 1997). Nevertheless, few studies have investigated the gravitational responses of bryophytes even though gravitropism has been extensively examined (Banbury 1962; Cove and Quatrano 2006; Martin et al 2009; Repp et al 2004; Schwuchow et al 2002); only one study showed the significant effect of microgravity on the growth pattern of the dark-grown protonemata of the moss Ceratodon purpureus (Kern et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes evidence the accumulation of γoryzanol derivatives during drying under solar exposition that can be attributed to the sunlight effect on ferulic acid metabolism and further synthesis of individual γ-oryzanol components. It has been reported that sunlight has a profound effect on the biosynthesis of ferulic acid esters by affecting the metabolic activation of enzymes involved in the defence mechanism to radiation (Wang et al, 2014), and also in the development of new plant structural tissues (Hoson and Wakabayashi, 2015). To our knowledge, this is the first report describing the effect of sun-drying on γ-oryzanol content and composition evidencing GBR as a rich source of γ-oryzanol.…”
Section: Discussionmentioning
confidence: 73%
“…10 3 Gal is the Earthly gravitational acceleration (Zharkov ), are, in practice, of no significance for living process, including those of plants. However, this view hardly takes account of anything other than the superficial appearance of biological organisms, all of which are constructed in such a way that they actually resist physical forces such as gravity (Hoson & Wakabayashi ), as well as exposure to varying atmospheric and hydrostatic pressures.…”
Section: Discussionmentioning
confidence: 99%